2008
DOI: 10.1093/her/cyn018
|View full text |Cite
|
Sign up to set email alerts
|

What is needed for informed decisions about prostate cancer screening: perspectives of African-American and Hispanic men

Abstract: Professional guidelines suggest that men should learn about risks and benefits of screening to make informed decisions consistent with their preferences. We used concept mapping to investigate views of informed decision making (IDM) of minority men. Statements about what men need for IDM about prostate cancer screening were sorted by similarity and rated for importance by 16 Hispanic and 15 African-American men. Multidimensional scaling and cluster analysis were used to develop a concept map for IDM. The 10-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…We engaged community members in the formative work leading up to the development of our intervention [22,40]. Working with community members during the course of designing and conducting research is one practical way to incorporate the values and priorities of marginalized ethnic and socioeconomic communities [39,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We engaged community members in the formative work leading up to the development of our intervention [22,40]. Working with community members during the course of designing and conducting research is one practical way to incorporate the values and priorities of marginalized ethnic and socioeconomic communities [39,41].…”
Section: Discussionmentioning
confidence: 99%
“…Women were included because prior research had indicated that women's perspectives on screening differed from men's and that their support is important for IDM [21,22]. We conducted a systematic review of empiric and theoretical/concept papers to identify cognitive and behavioral processes that comprise IDM, and 16 Hispanic men participated in concept mapping activities concerning what men need to make informed decisions about screening [22].…”
Section: Formative Researchmentioning
confidence: 99%
“…It can even be used as a reliable and valid method for analysing and interpreting open-ended survey data and for informing the development of qualitative interview questions (Jackson & Trochim 2002). The participatory elements of the method have been found useful in studies of community health issues (Burke et al 2005;Kelly et al 2007;McFall et al 2009;Vaughn, Jacquez & McLinden 2013;Vaughn & McLinden 2016) which many community-academic research partnerships address. This may be because concept mapping offers more than a simple method of data collection; it is a powerful visual tool that helps members of the stakeholder group comprehend what they deem to be collectively important so that they can take action.…”
Section: Concept Mappingmentioning
confidence: 99%
“…When conducted in collaborations between high-risk communities and academic partners CBPR-based recruitment may address factors of distrust, especially when the target population has experienced negative interactions with “research” [5,6,8,9,1835]. This is of particular relevance when racial and ethnic minorities, such as AAs, are the focus of recruitment efforts.…”
Section: Introductionmentioning
confidence: 99%